The Abundance Of Phytoplankton In Media Of Peat Soil Given Different Vermikompos - Hamsar Susilo Dinata; Saberina Hasibuan; Syafriadiman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in January to March 2017, located in thevillage of Qualu Nenas, Tambang Subdistrict, Kampar District, Riau Province.Phytoplankton observation was conducted in Environmental Quality Laboratoryof Cultivation, Faculty of Fisheries and Marine University of Riau. Method thisresearch using a Complete Randomized Design (CRD) was one factor with 4levels of treatment. The kinds of using are P0 (without giving the vermicompos),P1 vermicompos from human feces (0,615 kg m-2), P2 vermicompos from cowfeses (0,615 kg m-2) and P3 vermicompos from chicken feses (0,615 kg m-2).The best of treatment of this research was the P1 vermicompos from human feces(0,615 kg m-2). Phytoplankton abundance this treatment is 17.520 individu/L,rather than of the other treatment. The water quality parameters in this research isgood, especially of temperature 27-32 0C, pH 3.6-6,8, dissolved oxygen 2,0-3,3mg/L, nitrate 4.66-10,44 ppm and orthoposfat 2,50-6,76 ppm. refering for theQuality Standart of Aquaculture.Keywords: Vermikompos, Phytoplankton, Peat soil, Water quality